Comparative Biochemical Profile of Ascaridia galli Infected Broiler Chickens on Administration of Pineapple and Neem Leaves and Piperazine - Ali, M. Ayub; Devi, L. Inaotombi; Lyngdoh, W.M.; Das, Gunjan; Prasad, H.; Chanu, Kh. Victoria; Prava, M.; Tolenkhomba, T.C.; Singh, Y. Damodar; Lallinchhunga, M.C. (International Journal of Poultry Science, 2011)
A study was carried out to evaluate the change in serum biochemical profile of broiler chickens experimentally infected with Ascaridia galli on treatment with powdered leaves of neem and pineapple and with piperazin hydrate. The control and birds treated with piperazine, neem and pineapple show changes in the level of glucose, cholesterol, total protein, albumin, magnesium, potassium and SGPT. The piperazine treated groups can resist better the decreased in the glucose level compare to the groups treated with neem and pineapple. The serum cholesterol level of the control and treated birds shows increased in level while the total protein and albumin contents decreased in control and treated groups. However the decreased in the neem treated group was higher for total protein while the pipeapple treated group shows higher decrease in the level of albumin. The serum level of the potassium and SGPT level also changes in control as well as treated groups.